2008
DOI: 10.1677/joe-07-0552
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an adult stem/progenitor cell-like population in the human thyroid

Abstract: There is evidence that tissue-specific stem cells reside in certain adult tissues. Their specific properties remain elusive, because they are rare and heterogeneous in parent tissues; furthermore, technical difficulties have been encountered in the identification and characterization of their progeny. The aim of this study was to isolate stem/progenitor cells from the human thyroid. We devised a method based on the enzymatic digestion of fresh surgical thyroid specimens, followed by culture of cells in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 56 publications
3
39
0
Order By: Relevance
“…These cells reside in all tissues and organs and are capable of proliferating during the lifetime of the organism (Levi & Morrison 2008). Stem cells have been identified in the human thyroid gland (Thomas et al 2006, Lan et al 2007, Fierabracci et al 2008 and cancer stem cells in thyroid cancer cells and tissues (Mitsutake et al 2007, Todaro et al 2010, Zheng et al 2010, Malaguarnera et al 2011. Orthotopic transplantation of stem cells derived from undifferentiated thyroid cancer tissues into a mouse thyroid gland recapitulated the nature and behaviour of the original tumour, which supported the concept of stem cells being the source of tumour formation (Todaro et al 2010, Derwahl 2011.…”
Section: Introductionmentioning
confidence: 80%
“…These cells reside in all tissues and organs and are capable of proliferating during the lifetime of the organism (Levi & Morrison 2008). Stem cells have been identified in the human thyroid gland (Thomas et al 2006, Lan et al 2007, Fierabracci et al 2008 and cancer stem cells in thyroid cancer cells and tissues (Mitsutake et al 2007, Todaro et al 2010, Zheng et al 2010, Malaguarnera et al 2011. Orthotopic transplantation of stem cells derived from undifferentiated thyroid cancer tissues into a mouse thyroid gland recapitulated the nature and behaviour of the original tumour, which supported the concept of stem cells being the source of tumour formation (Todaro et al 2010, Derwahl 2011.…”
Section: Introductionmentioning
confidence: 80%
“…The role of embryonic stem cells and adult stem cells in the development of CSCs remains controversial. 6,[13][14][15] Recent studies have suggested that the stem cell programs operating in tumor-initiating cells (TICs) and non-neoplastic stem cells of the corresponding normal tissues are likely to differ significantly. 6 Solid tumors are usually heterogeneous at the histological, as well as the molecular level.…”
mentioning
confidence: 99%
“…The presence of thyroid SC populations was first postulated by Dumont et al (24), who found that it was possible to grow thyroid tissue in recipient animals using only a minimum number of cells. This idea was further elaborated and reinforced by Thomas et al (25) and Fierabracci et al (26) who identified precursor cells of endodermal origin and isolated a specific subset of cell populations from goitrous nodules that have the ability for clonal expansion respectively. These cells detected by flow cytometry comprise of less than 1.5% of human thyroid tissues and lack the expression of thyroid specific markers such as thyroglobulin (Tg).…”
Section: Normal Thyroid Scmentioning
confidence: 89%